Penguasaan Tanah Negara oleh Warga di Kampung Baru Harjamukti Depok: Studi Kepastian Hukum dan Keadilan Sosial - Sihombing, Petrus Roni Kristian; Widjojo, Anne Gunadi Martono (SIGn Jurnal Hukum, 2025)
The occupation of state land in urban Indonesia often generates complex conflicts between residents’ needs and the demands of formal legality, with implications for legal certainty and social justice. This study comprehensively analyzes the occupation of state land by residents in Kampung Baru Harjamukti, Depok, to examine the attendant problem of legal certainty, identify its implications for the realization of social justice for residents, and evaluate land governance in order to formulate an integrative solution model. Utilizing a normative legal research method that incorporates statute, conceptual, and limited case approaches, this study examines primary, secondary, and tertiary legal materials. It finds that thousands of residents have occupied state land without a valid title since the 1990s, a situation driven by informal transactions and complicated by a historical land legacy. Key findings indicate that this ambiguous legal status directly causes 4,800 residents, including 1,800 individuals without official residency documents, to lose access to essential public services and experience systemic marginalization, reflecting a social justice deficit. Furthermore, the study identifies weak inter-agency coordination and the ineffective exercise of governmental authority in conflict management. It is concluded that the agrarian conflict in Kampung Baru is a multidimensional crisis that demands an integrated solution—encompassing comprehensive land data collection, legalization of residents’ identity, and participatory cross-agency mediation—to sustainably achieve both legal certainty and social justice.